Unprivatizing - Virginia Leigh Hamilton Crowe; Jeanne Ellen Bitterman (Grounded Theory Review: An International Journal)
Depression is a complicated condition situated in a cultural environment that often impedes learning. The purpose of this grounded theory study was to better understand depression from the perspective of those who are living with depression. Data were collected from many sources including document review and autobiographical literature; however, the primary data were collected through in-depth interviews. Fifteen individuals, thirteen women and two men, who felt they had learned both about and from their depression volunteered to participate in the primary interview process. Analysis of the data generated categories, properties and the core concept of unprivatizing. Through theoretical coding a process of learning about one’s depression emerged which suggests that learning about one’s depression can be experienced as a transitional and meaning-making process that occurs over an extended period of time and facilitates development.